Teaching-learning process in times of a pandemic - Ramón Santiago, Pedro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article analyzes the teaching-learning process during the covid-19 pandemic (2020-2021) of a university in Tabasco, Mexico. The research was quantitative and descriptive-explorative. The information was collected through questionnaires sent through Google Forms to 70 professors and 391 students. Modifications were found in the class plans, in the teaching process and in the evaluations made by professors, taking into account criteria that wasn’t evaluated prior to the pandemic. The factors that intervened in the learning of students were the excess of homework (80%); difficulty to adapt to the new teaching system (46.6%); and the constant power failures (66.6%).